PREPARATION OF LEARNING OUTCOMES BASED ON THE PROTOTYPE CURRICULUM AT PAUD MUTIARA FOR THE 2022/2023 SCHOOL YEAR - Hasti Yustina; Desi Nuzul Agnafia; Normila Normila; Iswandi Fataruba (Jurnal Multidisipliner Bharasa, 2022)
ABSTRACT The new curriculum  is needed as a way out of the  learning process that is in line with the demands of the times and pandemic conditions, where changes in regulations and the learning process can occur at any time. This paper aims to explain the concept of the Prototype Curriculum at the PAUD level which is implemented in PAUD Mutiara Yogyakarta for the 2022/2023 Academic Year. This research uses a normative or literature approach, with primary data sources in the form of documents related to the research  focus.  The results  showed that through the Driving  School Program, a new curriculum concept called the Prototype Curriculum was obtained. At the PAUD level, the learning process is directed at 3 (three) Learning Outcomes (CP), namely: religious values and ethics; identity; the basis of STEAM literacy (science, technology, engineering, art, mathematics).  Learning Outcomes themselves have been previously known through the 2013 Curriculum with the terms Basic Competencies (KD) and Core Competencies (KI).   Abstrak Kurikulum baru ini diperlukan sebagai jalan keluar dari proses pembelajaran yang sejalan dengan tuntutan zaman dan kondisi pandemi, dimana perubahan regulasi dan proses pembelajaran dapat terjadi sewaktu-waktu. Tulisan ini bertujuan untuk menjelaskan konsep Kurikulum Prototipe di tingkat PAUD yang diterapkan di PAUD Mutiara Yogyakarta untuk Tahun Akademik 2022/2023. Penelitian ini menggunakan pendekatan normatif atau literatur, dengan sumber data primer berupa dokumen yang berkaitan dengan fokus penelitian.  Hasil penelitian menunjukkan bahwa melalui Program Driving School diperoleh konsep kurikulum baru yang disebut Kurikulum Prototipe. Pada tingkat PAUD, proses pembelajaran diarahkan pada 3 (tiga) Capaian Pembelajaran (CP), yaitu: nilai-nilai agama dan etika; identitas; dasar literasi STEAM (sains, teknologi, teknik, seni, matematika).  Capaian Pembelajaran sendiri sebelumnya telah dikenal melalui Kurikulum 2013 dengan istilah Kompetensi Dasar (KD) dan Kompetensi Inti (KI).